Maṣlaḥah dan Mafsadah Pemanfaatan Artificial Intelligence dalam Jual Beli Online: Perspektif Hukum Ekonomi Syariah - Achmad Fatich Asshidqi; Muhajir; Septian Fiktor Riyantoro (Kartika: Jurnal Studi Keislaman, 2026)
The development of Artificial Intelligence (AI) in digital trading transactions presents both opportunities and challenges from the perspective of Islamic Economic Law. AI is widely utilized in e-commerce through product recommendation systems, dynamic pricing mechanisms, chatbot-based customer services, and consumer data management. This study aims to analyze the use of AI in buying and selling transactions from the perspective of Islamic Economic Law using a maqāṣid al-sharī‘ah approach, particularly in examining the forms of benefit (maṣlaḥah) and potential harm (mafsadah) arising from its implementation. This research employs a qualitative method with a library research approach and adopts a normative-philosophical framework. Data sources include the Qur’an, Hadith, DSN-MUI fatwas, the Compilation of Sharia Economic Law, relevant digital economy regulations, as well as academic books and scholarly journals. The findings indicate that the use of AI in commercial transactions is fundamentally permissible (mubāḥ) under Islamic law as long as it promotes efficiency, justice, transparency, and consumer protection, thereby aligning with the objectives of ḥifẓ al-māl and taḥqīq al-maṣlaḥah. However, AI also poses potential risks such as gharar (uncertainty), algorithmic bias leading to injustice, data exploitation, and ambiguity in legal accountability. Therefore, the utilization of AI in trade must be governed by Islamic legal principles, ethical considerations, and adaptive regulatory frameworks to ensure that technological advancement remains consistent with the objectives of Islamic law.